KONSEP PERLINDUNGAN HUKUM TERHADAP PENGETAHUAN TRADISIONAL MASYARAKAT ASLI TENTANG OBAT DI INDONESIA - ZAINUL DAULAY (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2012)
The Protection of Traditional Knowledge, especially protection traditional medicine, have been an academic debate in international forum. Research is aimed to find out: firstly, living norms protecting traditional konowledge of medicine in indigenous communities; secondly, comparing practices of developing countries in regulating Traditional Knowledge; and thirdly, identifying the current applicable concept in protection Traditional knowledge. The finding of the research comprises, firstly, as a valid owner of traditional knowledge, indigenous peoples have reseonable rights to determine legal protection based on their perpectives. Secondly, practices of medicinal knowledge arrangement in developing countries are variable and; thirdly defensive protection concept and positive protection involves intellectual property regime (patent, trademark and geographical indication) and legal regime sui generis to be applied in traditional knowledge, especially medicinal knowledge.Key Words: Traditional Knowledge; Indigenous Peoples; Ownership; Intellectual Property, Legal Protection.